THE PHENOMENON OF FEAR OF MISSING OUT (FOMO) IN E-COMMERCE FLASH SALE STRATEGIES: A LITERATURE REVIEW OF CONSUMER PYSCHOLOGY - Chandra, Haura Rizqi Dzakiyyah; Bene Dicta Ary Susanti; Andika Adam Firdaus; Jeger Situmorang; Beryl Dani Athallah Zhahran; Rusdi Hidayat Nugroho (EZRA SCIENCE BULLETIN, 2025)
Fear of Missing Out (FOMO) is becoming increasingly prominent in the digital marketing, particularly in promotional strategies through flash sales implemented on e-commerce platforms. This article aims to review the literature related to the role of FOMO in influencing impulsive buying behavior among consumers on e-commerce platforms such as Shopee, Tokopedia, and TikTok Shop. The method used is a literature review by analyzing 20 selected journal articles published in the period 2021-2025. The results of the study show that FOMO consistently plays a major role as a trigger for impulsive behavior, especially when combined with urgency-based marketing strategies such as flash sales, scarcity, and promotions on twin dates. Other supporting factors such as hedonistic motivation, influencer content, and social media exposure further reinforce consumers' tendency to make spontaneous purchases. This study confirms that FOMO is not merely an emotional phenomenon but a strategic psychological mechanism utilized in digital marketing.